2021
DOI: 10.1111/cen.14605
|View full text |Cite
|
Sign up to set email alerts
|

Serum testosterone and oestradiol predict the growth response during puberty promoting treatment

Abstract: Objective: The influence of androgens and oestrogens on growth is complex, and understanding their relative roles is important for optimising the treatment of children with various disorders of growth and puberty.Design: We examined the proportional roles of androgens and oestrogens in the regulation of pubertal growth in boys with constitutional delay of growth and puberty (CDGP). The study compared 6-month low-dose intramuscular testosterone treatment (1 mg/kg/month; n = 14) with per oral letrozole treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A consequence of the apparent biphasic dose-response curve is that complete suppression of estrogen exposure may be less beneficial for growth than partial suppression. A recent study showed indeed that a threshold level of estrogen of 10 pmol/L appeared to be needed for an optimal growth rate corresponding to a normal male pubertal growth spurt ( 24 ). I shall come back to this issue in paragraph 3, where the use of AIs is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…A consequence of the apparent biphasic dose-response curve is that complete suppression of estrogen exposure may be less beneficial for growth than partial suppression. A recent study showed indeed that a threshold level of estrogen of 10 pmol/L appeared to be needed for an optimal growth rate corresponding to a normal male pubertal growth spurt ( 24 ). I shall come back to this issue in paragraph 3, where the use of AIs is discussed.…”
Section: Introductionmentioning
confidence: 99%